Bolaño and Borges: The Life of Infamous Characters - Arce Oses, Sebastián (2022)
A comparison is made of La literatura nazi en América, by Roberto Bolaño, and Historia universal de la infamia, by Jorge Luis Borges. Attention is given to the form and characteristics of the first part of Borges' book, the seven biographical sequences developed as narrative, ludic exercises, and specifically, the analysis of "El atroz redentor Lazarus Morell." Regarding Bolaño, consideration is given to the three “lives” of the first series of fictitious biographies, “Los Mendiluce.” We are interested in understanding them from the generic viewpoint: in their form, what joins or distinguishes them? What did Bolaño take from Borges?